Econometric Estimates of Deterrence of the Death Penalty: Facts or Ideology? - Gebhard Kirchgässner
In 2007, the Wall Street Journal published an article claiming that each execution saves more than 70 lives. This example is used to show how easy it is, using simple or advanced econometric techniques, to produce results that do or do not support the deterrence hypothesis. Moreover, we also point to some puzzles which have not been satisfactorily solved so far. We then present a critical survey of the papers published in the last ten years. It is shown how simple changes can produce quite different results using the same data. Finally, we draw some conclusions about the usefulness of statistical arguments in policy debates, but also on the moral questions involved in this particular debate.death penalty, deterrence, econometric evidence, ideology